Identiteta in pogovorni sistemi umetne inteligence - Centa Strahovnik, Mateja (Bogoslovni vestnik, 2023)
This paper explores the evolving perception of artificial intelligence (AI) systems in our increasingly AI-driven world, focusing on conversational AI or chatbots. With the rise of human-like robotic AI systems, there is a growing need to understand the identity these machines assume as they take on roles previously reserved for humans, such as caring for the elderly and educating children. The central thesis posits that comprehending the identity of such AI systems necessitates considering the aspect of our own identity that we shape and project onto them in our interactions with these systems. In an era defined by AI, these inquiries into identity and AI-human interactions are of paramount importance and are also vital for the very development of AI.
Keywords: artificial intelligence; chatbots; ethics; etika; identiteta; identity; klepetalni roboti; large language models; umetna inteligenca; veliki jezikovni modeli